Teaching Poetry in ELT Classrooms: Some Challenges and Solutions - Bastian Sugandi; . Husnaini (Bandar Lampung University, 2015)
Literature is one of the important things in the ELT classrooms. One of literary activities that EFL teachers can do to help students in learning English is through learning poetry. In ELT classrooms, teaching poetry is a challenge for teachers and a challenge for students to be learnt. There are some challenges in teaching poetry in ELT classrooms such as teachers and students should have extra thinking to get the meaning of poem that they read, they get difficulty because of linguistic aspects, some students feel bored in reading poetry activities, and teachers do not have the confidence to struggle. This paper presents not only some challenges but also some solutions to overcome with the challenges faced by teachers and students in teaching and learning poetry in ELT classrooms.